Bagaimana Generasi Milenial Membeli Makanan Halal? Peran Religious Belief, Subjective Norm, dan Halal Awareness - Annisa Nurhidayana; Rosa Prafitri Juniarti (Program Studi Magister Manajemen FE Unsri, 2020)
Halal is a recommendation for Muslim consumers. If the Muslim population increases, the awareness to consume halal food also increases. This research aims to analyze and discuss the influence of religious belief, subjective norm, and halal awareness with purchase intention halal food. The sampling technique used is non-probability sampling with a judgemental sampling method. The sampling used is 250, which has two criteria: Muslim and age 20-40 years. Data were analyzed using multiple linear regression analysis with the SPSS program. This study shows the relationship between religious belief and purchase intention, subjective norm and purchase intention, halal awareness, and purchase intention are significant. This research contributes to the halal food literature study, which also received special attention from young people. Even though young people tend to like to try new things, they still consider the halal products they consume. This finding also has important implications for marketers in Muslim countries.